2023
DOI: 10.1039/d3bm00610g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strontium substitution on functional activity of phosphate-based glass

Abstract: The optimization of strontium-substituted phosphate-based glass (PSr) can augment the bioactive cellular response by enhancing osteogenic differentiation and resisting the pro-inflammatory cytokine and improve the regenerative healing response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Strontium-doped phosphate glass has the potential for active ion delivery and promotion of bone formation [ 11 , 12 ]. Previous research succeeded in making phosphate glasses with up to 5 mol% of strontium which showed low cytotoxicity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strontium-doped phosphate glass has the potential for active ion delivery and promotion of bone formation [ 11 , 12 ]. Previous research succeeded in making phosphate glasses with up to 5 mol% of strontium which showed low cytotoxicity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%